Integrative Teaching Approach in Junior High School English Course Under the Big Ideas Perspective -Take Unit Two I'll Clean up the City (Asian Education Studies, 2022)
The new Curriculum Reform emphasizes junior high school students' learning and requires teachers to focus on guiding junior high school students' learning in the classroom. For junior high school English courses, teachers must improve students' language skills, deepen their minds, and develop their cultural awareness and independent learning ability. A good classroom atmosphere and a logical framework of knowledge can help junior high school students improve their English learning efficiency and increase their confidence in learning, thus promoting a beneficial learning cycle. Thus, junior high school English courses teachers must have a comprehensive knowledge of teaching and learning, optimize the teaching process and use appropriate activities to improve junior high school students' English ability. Teaching practice guided by the Big Ideas perspective helps students build the overall English knowledge framework. Therefore, teachers should focus on Big Ideas and integrate them with the unit content to make the course content focused and hierarchical so that junior high school students' English core competencies can be developed. This paper explores the integrative teaching approach to units in junior high school English courses from the perspective of Big Ideas. Based on the definition of Big Ideas and the practical value of the integrative teaching approach, the paper incorporates specific cases to illustrate how to practice the Integrative Teaching Approach, thus achieving a practical course.